Studieopdracht : Beatrixkwartier - Schenkstrook. (Den Haag : Stroom hcbk, 1994)
Pfannenmüller, Urs ; Veldhoen, David ; Dirker, Onno ; van Grunsven, Jan ; van der Mark, Arno ; Pollack, Linda ; de Lyon, Erick
boek
Keywords: Den Haag